China's rising Foreign Ministry practices and representations of assertive diplomacy - Loh, Dylan M. H. (Studies in Asian security., 2024)
"China's rise and its importance to international relations as a discipline-defining phenomenon is well recognized. Yet when scholars analyze China's foreign relations, they typically focus on Beijing's military power, economic might, or political leaders. As a result, most traditional assessments miss a crucial factor: China's Ministry of Foreign Affairs (MOFA). In China's Rising Foreign Ministry, Dylan M.H. Loh upends conventional understandings of Chinese diplomacy by underlining the importance of the ministry and its diplomats in contemporary Chinese foreign policy. The book explains how MOFA gradually became the main interface of China's foreign policy and the primary vehicle through which the idea of 'China' is produced, articulated, and represented on the world stage. Through a multi-year and multi-sited fieldwork study of China's MOFA, this groundbreaking book investigates the practices and experiences of the actors that produce diplomacy and documents the ministry's evolution into one of the most significant institutions in China's rise. A theoretically innovative and ambitious book, China's Rising Foreign Ministry contributes an original reading of Chinese foreign policy, with wide-ranging implications for international relations. By shedding light on the dynamics of Chinese diplomacy and how assertiveness is constructed, Loh provides readers with a comprehensive appraisal of China's foreign ministry and the role it performs in China's re-emergence"-- Provided by publisher.